Students’ Perception Towards the Use of Spotify Application as A Medium of Listening Practice A Case Study in 2nd Semester English Education of the University Mataram - Awindya, Alzena; Arafiq; Aziz, Atri Dewi; Sahrul (Journal of English Education Forum (JEEF), 2024)
A common issue faced in the English study program is students' lack of understanding in listening, as evidenced by low scores in the listening section of the TOEFL test. Additionally, students often engage in activities requiring strong listening skills to comprehend speakers and interact effectively with others. To address this, researchers have chosen Spotify as a tool for enhancing listening skills due to its accessibility at any time and place. This study aimed to explore students' perceptions and development while using Spotify for listening practice. Utilizing qualitative methods and purposive sampling, as only a few students use Spotify, the findings revealed that most respondents strongly agreed or agreed that Spotify is an effective medium for improving their listening skills. Positive feedback from interview responses further supports the idea that Spotify is a suitable tool for listening practice. The study's results indicate that respondents have a positive perception of Spotify as a medium for listening practice, as it offers a wide variety of songs and podcasts across different genres. Respondents predominantly agreed that Spotify helps improve their English skills, particularly in listening and vocabulary, while also providing a comfortable and motivating environment for learning.